2016
DOI: 10.1080/23761407.2016.1166841
|View full text |Cite
|
Sign up to set email alerts
|

Animal Assisted Therapy and Trauma Survivors

Abstract: Animal therapy is making strides in the treatment of posttraumatic stress disorder (PTSD). For years, animals have been used with great benefit in the treatment of the aged and the terminally ill. Now animal assisted therapy is benefitting sufferers of PTSD. The results of animal assisted therapy in the treatment of PTSD patients have seen significant results. In one study of the effect of dogs with patients, psychologists noted an 82% reduction in symptoms. One particular case noted that interacting with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
1
8
0
3
Order By: Relevance
“…Many studies have underlined the benefits for humans from AAIs [2]; they can improve the ability to socialize or communicate, or help with motor rehabilitation (see, for example, [2,3,4,5,6,7,8,9,10]). Furthermore, they can also improve impulse control, enhance self-esteem, and decrease feelings of anger and symptoms of depression and/or anxiety (see, for example, [11,12,13,14,15,16,17,18,19,20,21]).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have underlined the benefits for humans from AAIs [2]; they can improve the ability to socialize or communicate, or help with motor rehabilitation (see, for example, [2,3,4,5,6,7,8,9,10]). Furthermore, they can also improve impulse control, enhance self-esteem, and decrease feelings of anger and symptoms of depression and/or anxiety (see, for example, [11,12,13,14,15,16,17,18,19,20,21]).…”
Section: Introductionmentioning
confidence: 99%
“…Foram considerados metodologicamente fortes os trabalhos que apresentassem escore igual ou superior a 80% da pontuação máxima, escores entre 60 e 80% como moderados e aqueles inferiores a 60% foram considerados metodologicamente insatisfatórios (fracos). Para o presente estudo, as questões referentes aos ensaios clínicos (8,9,14,15,23,24,26,27) não foram utilizadas. Deste modo, foram considerados 19 itens da escala original, fornecendo uma pontuação máxima de 20 pontos, visto que a pergunta 5 permite pontuação de 0 a 2 [13].…”
Section: Bases De Dadosunclassified
“…Diversas terapias alternativas estão sendo exploradas, entre elas a Terapia Assistida por Animais. Estudos como o de Mims e Waddell apontam os benefícios das Intervenções Assistidas por Animais (IAAs) e relatam que, após acariciar um animal de terapia, houve a liberação de endorfina, fazendo com que as pessoas se sentissem melhor, diminuindo a sensação de dor, depressão e solidão [8]. Também foi observado por Odendaal e Meintjes que acariciar um cão ou gato estimulou a produção de ocitocina [9].…”
Section: Introductionunclassified
“…There have been many research studies documenting positive effects of AAI on symptoms of post-traumatic stress disorder (PTSD), with the majority focused on military veterans and service members (Altschuler, 2018;Germain, Wilkie, Milbourne, & Theule, 2018;Knisely, Barker, & Barker, 2012;Husband, Ahmed, & Dell, 2019;Krause-Parello, Sarni, & Padden, 2016;Mims & Waddell, 2016;O'Haire et al, 2015;O'haire & Rodriguez, 2018;Yount, Olmert, & Lee, 2012). Other research has found benefits for children and youth who have experienced trauma (Hoagwood, Acri, Morrissey, & Peth-Pierce, 2017;Lentini & Knox, 2015;Signal, Taylor, Prentice, McDade, & Burke, 2016).…”
Section: Animal-assisted Interventionsmentioning
confidence: 99%